Anna Akhmatova in the Perception of Lithuanian Prose Writer, Translator Juozas Tininis - Ivinskaia, Aliona Sofia (Literatūra, 2024)
The article examines the historical and cultural context of the study of Akhmatova by the Lithuanian prose writer and translator Juozas Tininis, and discusses the translations of the Russian poet’s poems in it. By the time of its publication in 1967, Tininis’ article on Akhmatova was the first Lithuanian study covering the entire work of the Russian poet. Tininis identified the stages of her creative evolution and thus brought the Lithuanian reader to one of the important features of her poetry: cyclization. A cursory analysis of Tininis’ translations of Akhmatova’s poems indicates that the Lithuanian author chose for translation those poetic fragments that, in his opinion, illustrate the main feature of Akhmatova’s style: laconicism in revealing the complex emotional world of a person.